3D biomechanical analysis of women's high jump technique - Panoutsakopoulos, V.; Kollias, I. A. (New Studies in Athletics, 2012)
The purpose of the present study was to investigate the three-dimensional kinematics of contemporary high jump technique during competition and to compare the results with findings from previous elite-level events. The participants in the women's high jump event of the European Athletics Premium Meeting "Thessaloniki 2009" served as subjects. The jumps were recorded using three stationary digital video cameras, operating at a sampling frequency of 50fields/sec. The kinematic parameters of the last two strides, the take-off and the bar clearance were extracted for analysis through software. The results indicated that the kinematic parameters of the approach (i.e. horizontal velocity, stride length, stride angle, height of body centre of mass) were similar to those reported in the past. However, a poor transformation of horizontal approach velocity to vertical take-off velocity was observed as a greater deceleration of the swinging limbs could be seen at the instant of take-off. Considerable backward lean at take-off, large takeoff angle and inefficient bar clearance were also noted. The authors recommend that the athletes studied consider giving a greater emphasis to the key technique elements of the take-off phase and of the bar clearance.